2006
DOI: 10.1002/rob.20150
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable ankle rehabilitation robot for various exercises

Abstract: This paper presents a reconfigurable ankle rehabilitation robot to cover various rehabilitation exercise modes. The designed robot can allow desired ankle and foot motions, including toe and heel raising as well as traditional ankle rotations, since the mechanism can generate relative rotation between the fore and rear platforms as well as pitch and roll motions. In addition, the robotic device can be reconfigured from a range of motion ͑ROM͒/strengthening exercise device to a balance/proprioception exercise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 26 publications
(18 reference statements)
0
72
0
2
Order By: Relevance
“…Symbols corresponding to actuated joints are underlined in this notation. work has been extended to allow for the reconfiguration of the device to support several distinct exercise modes including metatarsophalangeal mobilization (Yoon et al 2006). In particular, by changing and/or reorienting several components of the mechanism, the end-effector type device can be configured as an ROM/strengthening exercise device or as a mechanism that can be used to exercise balance/proprioception.…”
Section: Robot-assisted Ankle Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Symbols corresponding to actuated joints are underlined in this notation. work has been extended to allow for the reconfiguration of the device to support several distinct exercise modes including metatarsophalangeal mobilization (Yoon et al 2006). In particular, by changing and/or reorienting several components of the mechanism, the end-effector type device can be configured as an ROM/strengthening exercise device or as a mechanism that can be used to exercise balance/proprioception.…”
Section: Robot-assisted Ankle Rehabilitationmentioning
confidence: 99%
“…Rehabilitation of ankle injuries is typically addressed in three sequential phases (Mattacola and Dwyer 2002;Yoon et al 2006;Satici et al 2009): The early phase focuses on enabling the full RoM of the joint and strengthening the ankle muscles. The intermediate phase emphasizes the enhancement of proprioception ability through the use of static balance exercises and is initiated once the required RoM and flexibility are achieved and the muscles become strong enough to bear partial weight.…”
Section: Introductionmentioning
confidence: 99%
“…In particular they have used a central strut and analyzed three different types of parallel robots in the domains of stiffness. A single platform-based reconfigurable robot mechanism has been proposed by (Yoon et al, 2006). This robot design considers the MTP joint apart from the ankle joint motions and has less than six DOF motions.…”
Section: Ankle Rehabilitation Robotsmentioning
confidence: 99%
“…While Zhang et al [27] demonstrated the effectiveness of existing rehabilitation robots in reducing ankle impairments caused by neurological injuries, most of them suffer from a variety of limitations when used for the treatment of drop foot. Parallel robots with misaligned rotation centers with the ankle joint are unsuitable for this application [28][29][30], since that training using these devices usually requires synergic movement of the lower limb of patients Parallel robots whose rotation center coincides with the ankle joint is more suitable for treating drop foot, where the patient can place his/her shank on a leg holder. This kind of robots can have a single range of motion (DOF) or multiple DOFs.…”
Section: Introductionmentioning
confidence: 99%